Synthesis and Identification of a Novel Peptide, Ac-SDK (Biotin) Proline, That Can Elicit Anti-Fibrosis Effects in Rats Suffering from Silicosis - Wang J; Qian Y; Gao X; Mao N; Geng Y; Lin G; Zhang G; Li H; Yang F; Xu H (Dove Medical Press, 2020)
Jin Wang,1,2 Ye Qian,2 Xuemin Gao,3 Na Mao,3 Yucong Geng,4 Gaojie Lin,3 Guibin Zhang,2 Han Li,3 Fang Yang,3 Hong Xu3 1Department of Clinical Laboratory, Qingpu Branch of Zhongshan Hospital, Fudan University, Shanghai 201700, People’s Republic of China; 2Hebei Key Laboratory for Chronic Diseases, Tangshan Key Laboratory for Preclinical and Basic Research on Chronic Diseases, School of Basic Medical Sciences, North China University of Science and Technology, Tangshan, Hebei 063210, People’s Republic of China; 3Medical Research Center, International Science and Technology Cooperation Base of Geriatric Medicine, North China University of Science and Technology, Tangshan, Hebei 063210, People’s Republic of China; 4Department of Pathology, Haigang Hospital of Qinhuangdao, Qinhuangdao, Hebei, 066000, People’s Republic of ChinaCorrespondence: Hong XuMedical Research Center, International Science and Technology Cooperation Base of Geriatric Medicine, North China University of Science and Technology, Tangshan, Hebei 063210, People’s Republic of ChinaTel +86-315-8816236Fax +86-315-8816238; Email xuhong@ncst.edu.cnBackground: N-Acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) is a short peptide with an anti-silicosis effect. However, the short biological half-life and low plasma concentration of Ac-SDKP hamper discovery of specific targets in organisms and reduce the anti-silicosis effect. A novel peptide, Ac-SDK (biotin) proline, termed “Ac-B”, with anti-fibrotic properties was synthesized.Methods: Ac-B was detected quantitatively by high-performance liquid chromatography. Phagocytosis of Ac-B by the alveolar epithelial cell line A549 was investigated by confocal laser scanning microscopy and flow cytometry. To further elucidate the cellular-uptake mechanism of Ac-B, chemical inhibitors of specific uptake pathways were used. After stimulation with transforming growth factor-β 1, the effects of Ac-B on expression of the myofibroblast marker vimentin and accumulation of collagen type I in A549 cells were analyzed by Western blotting. Sirius Red staining and immunohistochemical analyses of the effect of Ac-B on expression of α-smooth muscle actin (SMA) in a rat model of silicosis were undertaken.Results: Ac-B had good traceability during the uptake, entry, and distribution in cells. Ac-B treatment prevented an increase in α-SMA expression in vivo and in vitro and was superior to that of Ac-SDKP. Caveolae-mediated uptake of Ac-B by A549 cells led to achieving anti-epithelial–mesenchymal transformation (EMT) effects.Conclusion: Ac-B had an anti-fibrotic effect and could be a promising agent for the fibrosis observed in silicosis in the future.Keywords: Ac-SDKP, biotin, epithelial–mesenchymal transformation, phagocytosis, anti-fibrotic function